Ascidian distribution provides new insights to help define the biogeographic provinces in the South American Region - Taverna, Anabela Jesús; Lagger, Cristian Fabian; Maggioni, Tamara; Reyna, Paola Beatriz; Lovrich, Gustavo Alejandro; Tatian, Marcos (Polar Biology)
The validity and size of the biogeographic Magellan Province of marine organisms have been the focus of discussion of many authors. The distribution of fish and other organisms has revealed a lack of homogeneity in the area, which has also been interpreted as comprising four different Provinces: Southern Chile (SCH), Tierra del Fuego (TDF), Southern Argentina (SAR), and the Malvinas/Falkland Islands (MAI). For the first time, we assess the ascidian fauna of this region to determine if the distribution of benthic sessile filter feeders corresponds to these biogeographic provinces. Ascidian species richness and percentages of endemism for these four areas were estimated using data from the literature and new sampling. Biogeographic affinities among SCH, TDF, SAR, and MAI were also calculated. The species Pyura pilosa, Molgula malvinensis, and Molgula manhattensis, the latter frequently considered as invasive, were found for the first time on the TDF shelf. The highest ascidian species richness was found in TDF (70 species), while the percentages of endemism greater than 10% (the minimum to qualify an area as a province) were found in TDF (15.7%) and SCH (11.1%). SAR and MAI showed the lowest percentages of endemism and the strongest affinity. Based on percentages of endemism, faunal affinities, and differences among the four provinces, we propose a separation of the South American Region into three Provinces: SCH, TDF, and SAR/MAI. Continued sampling of ascidians is considered to be particularly important, given the potential spread of invasive species throughout this region. Fil: Taverna, Anabela Jesús. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Diversidad y Ecología Animal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto de Diversidad y Ecología Animal; Argentina Fil: Lagger, Cristian Fabian. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico ...